A "metal ions-induced poisoning behavior of biomolecules" inspired polymeric probe for Cu2+ selective detection on basis of coil to helix conformation transition. (15th March 2022) - Duan, Huimin; Yin, Lijie; Chen, Tao; Qi, Dongming; Zhang, Dongyue
Graphical abstract: According to the bionic strategy inspired by a "metal ions-induced poisoning behavior of biomolecules", a newly found glycine-based water-soluble polyacetylenes are elaborately designed and synthesized to simulate the transition on secondary structure in the presence of Cu 2+ ions in aqueous solution. The "random coil to helical" conformation transition provided that the selective detection of new polyacetylene-type probe towards Cu 2+ exhibited an outstanding time-efficiency and reliability with the corresponding detection limitation around 0.128 mg/L. Highlights: Water-soluble substituted polyacetylene-type probe (P-Gly-NH2 ) for Cu 2+ detection was elaborately developed via a bionic strategy. Cu 2+ selective detection was realized by the "random coil to helical" conformation transition of P-Gly-NH2 . A specific and sensitive Cu 2+ detection was swiftly achieved on the basis of UV–vis characterization. Abstract: The interaction between heavy metal ions (e.g. Cu 2+, Pb 2+, Cr 6+ ) and bioactive biomolecules can severely cause the "poisoning behavior" due to the secondary structure transition. While in a bioinspiration strategy, functional polymers with the ability of selectively responding to metal ions can be used as effective probe candidate for metal ion detection. Herein, a series of functional substituted polyacetylenes with glycine pendants (P-Gly-NH2 ) are deliberately designed and synthesized as a fresh member of polymeric probe arsenal for selective ions recognition. According to chemical and structural characterization including FT-IR, NMR, GPC, UV–vis and so on, the synthesized P-Gly-NH2 polymers with glycine amide pendants possess random coil conformation on the conjugated main chains. Benefit from remarkable water-soluble ability and secondary structure, P-Gly-NH2 can simulate the biomolecules and apply for heavy metal ions detection in aqueous solution. Because of the complexing interaction with Cu 2+, the particular "random coil to helical" conformation transition of P-Gly-NH2 backbone can be observed by UV–vis characterization in ion recognition experiments. Moreover, the relevant results of ions interfering and titration experiments also confirm that this selective detection towards Cu 2+ exhibits an outstanding time-efficiency and reliability with the corresponding detection limitation around 0.128 mg/L. As revealed in UV–vis, Raman, FT-IR and XPS spectra characterization, this conformation transition of P-Gly-NH2 is owing to the complexing interaction between Cu 2+ and nitrogen atoms in polymer side groups, resulting in an ordered cis -cisoidal helical structures in polymer backbones. In a word, this study not only paves a new way for design and synthesis of water-soluble amino acid-based substituted polyacetylenes, but also implements the functional polymeric probes for selective and sensitive detection of heave ions through a bioinspiration strategy.